The great depression in Brazil - Astorino, Eduardo Sanchez (2012)
This work aims to explain the performance of the Brazilian economy throughout the period of the Great Depression. We propose a general equilibrium, open economy model in which the Brazilian government can improve the terms of trade by taking advantage of Brazil\'s monopolistic position in international coffee markets. It burns a share of coffee production in order to influence international prices, thus containing the impact of the Great Depression on the domestic economy\'s supply of foreign consumption and investment goods. We find that our coffee burning mechanism is capable of improving the performance of the economy for some of our assumptions about the share of coffee that is destroyed. Our models also fits with different degrees of success the data on international coffee prices.